Prevalence of Gastrointestinal Parasites of Stray Dogs in Suleja Metropolis, Niger State, Nigeria - Adesoye , Oluwaseun Adegbola; Olanrewaju, Comfort Adetutu; Ameh, Ugbede Christianah; Malann, Yoila David; Akinleye, Callistus Adewale; Akinsete, Israel O.; Adeniyi, Kamoru A.; Oyeniran, Oluwatoyin A. (Sahel Journal of Life Sciences FUDMA, 2024)
Free-roaming dogs in the environment (stray dogs) have been reported to be a reservoir of various gastrointestinal (GIT) parasites of significant public health importance worldwide. This study aims to determine the prevalence of GIT parasites in the stray dog population in Sabo Gwazunu, Suleja and within Suleja Township, of Niger State, Nigeria. Sixty fecal samples were randomly collected from stray dogs in each study area (community) between February and March 2024. The Sheather’s sugar floatation technique was used to examine various faecal samples, and the prevalence was calculated as the percentage of infected samples over the total number of samples examined. Overall, a total of thirteen GIT parasites belonging to Phylum Protozoa 3.33% (4/120), Platyhelminthes 3.33% (4/120), and Nematoda 4.16% (5/120), were found. A significant difference was observed in GIT prevalence between the study areas (P<0.05). GIT parasites found in stray dogs within Suleja township comprise Toxocara canis Eimeria sp, Strongyloides sp, Alaria sp, Cryptosporidium sp, Entamoeba sp, Ancylostoma sp, Dipylidium sp, Schistosoma sp, and Taenia sp. However, in Sabo Gwazunu, nine GIT parasites were found in stray dogs. These include Eimeria sp, T. canis, Trichuris sp, Physaloptera sp, Strongyloides sp, Dipylidium sp, Schistosoma sp, Alaria sp, and Taenia sp. Moreover, the prevalence of GIT in stray dogs in both communities was estimated at 91% (91/120). Given the public health and zoonotic significance of some gastrointestinal parasites observed in this study, it is essential to increase awareness about the need to control the stray dog population in the study areas.